Correction: Protective mechanisms of Zanthoxylum bungeanum essential oil on DSS-induced ulcerative colitis in mice based on a colonic mucosal transcriptomic approach. Issue 3 (19th January 2023) - Zhang, Huan; Guo, Zhiqing; Wang, Xiao; Xian, Jing; Zou, Liang; Zheng, Chuan; Zhang, Jinming
Abstract : Correction for 'Protective mechanisms of Zanthoxylum bungeanum essential oil on DSS-induced ulcerative colitis in mice based on a colonic mucosal transcriptomic approach' by Huan Zhang et al., Food Funct., 2022, 13, 9324–9339, ; https://doi.org/10.1039/D1FO04323D .